Middle East and North Africa Quarterly Economic Brief, July 2013 : Growth Slowdown Extends into 2013 - Devarajan, Shantayanan (Washington, DC: World Bank, 2014)
While the focus has been on the recent change in government in Egypt, five countries in the Middle East and North Africa Region, including Egypt, Tunisia, Lebanon, Jordan and Iran are facing a growth slowdown, rising fiscal deficits and debt, and high unemployment and inflation. Continued political turmoil in Egypt and spillovers from the civil war in Syria to Jordan and Lebanon threaten to make their economic situation worse. While easing political tensions in Tunisia and post-election improvements in Iran’s international relations may help these countries, the overall macroeconomic outlook in all five countries for the rest of 2013 is grim.